1976
DOI: 10.1111/j.1748-1716.1976.tb10321.x
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Vagal Adrenergic Release of Serotonin from Enterochromaffin Cells in the Cat

Abstract: The intracellular concentrations of serotonin (5-HT) in enterochromaffin cells (EC) in the cat small intestine have been studied by a cytofluorimetric method before and after long-lasting efferent vagal nerve stimulation in the neck. Such stimulation induces a decrease of 5-HT in EC of the gut as observed previously. Pretreatment with atropine could not block this decrease, suggesting a noncholinergic mechanism. Pretreatment with a beta-blocking agent, propranolol, or bilateral removal of the superior cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Desensitization of 5-HT receptors occurs when SERT is inhibited in the guinea pig distal colon in vitro, and when this does occur, the peristaltic reflex is blocked (Wade et al, 1996). Catecholamines strongly stimulate 5-HT release from EC cells (Ahlman et al, 1976;Racké et al, 1988;Racké and Schwörer, 1991), and sympathetic nerves innervate enteric serotonergic neurons (Gershon and Sherman, 1987). Infections or fright, which causes the release of catecholamines from sympathetic nerves or the adrenal medulla, might release enough 5-HT to overcome compensatory mechanisms in the SERT Ϫ/Ϫ bowel and desensitize enteric 5-HT receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Desensitization of 5-HT receptors occurs when SERT is inhibited in the guinea pig distal colon in vitro, and when this does occur, the peristaltic reflex is blocked (Wade et al, 1996). Catecholamines strongly stimulate 5-HT release from EC cells (Ahlman et al, 1976;Racké et al, 1988;Racké and Schwörer, 1991), and sympathetic nerves innervate enteric serotonergic neurons (Gershon and Sherman, 1987). Infections or fright, which causes the release of catecholamines from sympathetic nerves or the adrenal medulla, might release enough 5-HT to overcome compensatory mechanisms in the SERT Ϫ/Ϫ bowel and desensitize enteric 5-HT receptors.…”
Section: Discussionmentioning
confidence: 99%
“…vagal or sympathetic modulation of descending inhibitory pathways 11,32 . There is, however, evidence that efferent neural stimuli to the intestine have a direct effect on enterocyte secretion and motility 33–35 . Enterochromaffin (EC) cells are innervated by sympathetic and parasympathetic fibres.…”
Section: Discussionmentioning
confidence: 99%
“…Enterochromaffin (EC) cells are innervated by sympathetic and parasympathetic fibres. Isolated ileum EC cells and intact mucosa have been shown to release serotonin in response to norepinephrine, suggesting that sympathetic nervous system dominance may result in serotonin release and subsequent changes in motility and secretion 33–35 …”
Section: Discussionmentioning
confidence: 99%
“…Cytofluorimetric studies of duodenal EC have demonstrated decreased intracellular levels of 5-HT aflcer efferent electrical stimulation of the cervical vagi. This response was probably not cholinergic since it was unaffected by atropine pretreatment or by a selective adrenergic denervation of the cervical vagi by ectomy of superior cervical ganglia prior to the nerve stimulation in favour of an adrenergic mechanism (Ahlrnan et al, 1976 b). Also, in vitro incubations of gut biopsies with adrenergic agonists and antagonists followed by cytofluorimetric observations have indicated that EC are under adrenergic control, probably via /32 adrenoceptors .…”
Section: Discussionmentioning
confidence: 96%